Surgical Management of Extensive Facial Laceration: A Case Report - Silva, Emanoel Italo de Almeida; Cavalcante, Nayara Kelly Silva de Oliveira; Pereira, Rildenson Moura; Vidal, Iago Barbosa; Ferreira Filho, Josfran da Silva; Gondim, Ricardo Franklin; Menezes Junior, José Maria Sampaio; Mello, Manoel de Jesus Rodrigues; Carvalho, Abrahão Cavalcante Gomes de Souza (Brazilian Journal of Case Reports, 2025)
Tissue injuries are common consequences in the care of polytraumatized patients, with traffic accidents, falls, physical assaults, and animal bites being the main etiological factors. This study aims to report the surgical management of extensive facial laceration. A 42-year-old man was admitted to a referral hospital for emergency care in the state of Ceará, Brazil, following a motorcycle accident. On initial examination, the patient was unconscious, under mechanical ventilation via a definitive airway, and presented with multiple facial lacerations, including the midface, lateral border, lingual dorsum, and lower lip. Emergency surgical intervention was indicated for laceration suturing in the operating room. The procedure began with irrigation, debridement, and hemostatic control of the injuries. Sutures were performed sequentially, starting with the lingual dorsum and lateral border, followed by the lower lip, and concluding with layered sutures of the midface lacerations, beginning intraorally and continuing extraorally. A Penrose drain was placed on the right side due to involvement of the parotid gland in the laceration. The patient has been followed up in an outpatient setting for nine months, presenting satisfactory healing without pain or functional complaints. A meticulous understanding of facial anatomy and injury patterns is crucial to ensuring both function and aesthetics for the patient.